2021
DOI: 10.1093/advances/nmab068
|View full text |Cite
|
Sign up to set email alerts
|

Female Fertility and the Nutritional Approach: The Most Essential Aspects

Abstract: Infertility is an increasing problem that affects couples attempting pregnancy. A growing body of evidence points to a link between diet and female fertility. In fact, data show that a diet high in trans fats, refined carbohydrates, and added sugars can negatively affect fertility. Conversely, a diet based on the Mediterranean dietary patterns, i.e., rich in dietary fiber, omega-3 (ɷ-3) fatty acids, plant-based protein, and vitamins and minerals, has a positive impact on female fertility. An unhealthy diet can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 179 publications
(175 reference statements)
0
70
0
1
Order By: Relevance
“…Vitamins in the diet were supposed to have beneficial effects on women’s fertility ( Skoracka et al, 2021 ). Interestingly, the gut bacteria in pregnant sows appeared to be more correlated to the metabolism of cofactors and vitamins than the other two groups, and lactating sows appeared to have higher responses to bacterial infections, which may be more beneficial to improve the levels of maternal antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamins in the diet were supposed to have beneficial effects on women’s fertility ( Skoracka et al, 2021 ). Interestingly, the gut bacteria in pregnant sows appeared to be more correlated to the metabolism of cofactors and vitamins than the other two groups, and lactating sows appeared to have higher responses to bacterial infections, which may be more beneficial to improve the levels of maternal antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Research published in Advances in Nutrition, a peer-reviewed publication, investigates female fertility and the nutritional approach, which is gaining popularity throughout the world. Skoracka et al, 2021 have identified a potential link for a holistic approach to improving female fertility and overall fecundability for females of childbearing ambitions [ 204 ]. It has been established that the consumption of trans-fatty acids, processed carbs, and added sugars has a detrimental impact on female fertility.…”
Section: Trace Elements and Female Reproductive Organsmentioning
confidence: 99%
“…Independently of how strongly modified risk factors contribute to hypothyroxinemia and infertility, they should be, together with all other nutritional abnormalities, eliminated in women of childbearing age, especially in those planning pregnancy [52].…”
Section: Discussionmentioning
confidence: 99%